Pharmacokinetics and Tissue Residue Profiles of Enrofloxacin in Crucian Carp (Carassius auratus gibelio) Following Single and Multiple Oral Administration - Shan, Qi; Huang, Heqing; Zheng, Guangming; Yin, Yi; Zhu, Xinping; Ma, Lisha; Zhou, Hao; Xie, Wenping; Li, Lichun; Liu, Shugui; Wang, Jingxin (Frontiers in Veterinary Science, 2022)
The pharmacokinetics, tissue distribution, and elimination of enrofloxacin (ENR) and its metabolite ciprofloxacin (CIP) were investigated to the crucian carp (Carassius auratus gibelio) after single (20 mg/kg b. w.) and multiple oral administration (20 mg/kg b.w. one time daily for 5 days) at 28°C. The concentrations of ENR and CIP in the plasma and tested tissues (muscle/skin, liver, and kidney) were detected simultaneously by high-performance liquid chromatography (HPLC), and the pharmacokinetic data were analyzed with a non-compartmental model using WinNonLin 6.1 PK software (Pharsight Corporation, Mountain View, CA, USA). The pharmacokinetic characteristics of ENR in crucian carp exhibited slow absorption, wide tissue distribution, and long elimination half-life. In the single-dose group, the peak concentrations (Cmax) of ENR in the plasma, muscle/skin, liver, and kidney were 8.93 μg/mL, 13.9 μg/g, 31.2 μg/g, and 27.3 μg/g, respectively, observed at 3 h, 6 h, 1 h, and 3 h after dosing. The elimination half-lives (T1/2λz) of ENR in plasma, muscle/skin, liver, and kidney were calculated to be 67.4, 82.8, 94.4, and 114 h, respectively. In the multiple-dose group, the Cmax of ENR in the plasma, muscle/skin, liver, and kidney were 18.4 μg/mL, 26.8 μg/g, 82.8 μg/g, and 74.5 μg/g, respectively, achieved at 3 h, 6 h, 1 h, and 1 h after the last dose. The T1/2λz of ENR in the plasma, muscle/skin, liver, and kidney were calculated to be 76.4 h, 91.5 h, 114 h, and 148 h, respectively. During the multiple-dose administration, significant accumulations of ENR and CIP were observed in the plasma and tissues of crucian carp, possibly due to their long elimination half-lives. In both dose groups, the AUC0−∞ for both ENR and CIP followed the order of liver > kidney > muscle/skin > plasma. The finding suggested that the liver may play an important role in the metabolism of ENR. According to the calculated PK/PD indices of Cmax/minimum inhibitory concentrations (MIC) and AUC24h/MIC, the multiple-dose regimen would be highly effective against pathogenic bacteria with a MIC value of ≤ 1.84 μg/ml. Depletion studies indicated that a withdrawal period of at least 29 or 32 days was necessary to guarantee food security after single or multiple oral gavage administration at 28°C.